Leadership and ESG-Based Innovation (Environmental, Social, Governance): Implications for SME Performance in the START-UP Environment - Cahyono, Puguh; Ramadhani, Aringgi Dwi; Rochmawati, Inda; Febriyanty, Putri; Mas'ud, Akhmad Khoirul (PT. LITERASI SAINS NUSANTARA, 2024)
In recent years, the paradigm shift towards social and environmental responsibility has become a top priority across various sectors, including among SMEs and start-ups. The ESG concept, encompassing environmental, social, and governance aspects, has become a crucial foundation for developing sustainable business strategies. The importance of ESG-based leadership in SMEs lies in the ability of leaders to integrate ESG principles into the company’s culture and operations. This study aims to provide deeper insights into the strategies and best practices in ESG-based leadership and innovation and their implications for the success and sustainability of SMEs in an increasingly complex and dynamic context. The research employs a qualitative approach using a literature review method. Data is collected through a literature search on Google Scholar, covering the period from 2015 to 2024. The findings of the study indicate that first, effective leadership plays a crucial role in integrating ESG principles into SME strategies and operations. Visionary leaders can motivate teams, create a culture that supports sustainability, and ensure that ESG practices are consistently applied. Second, ESG-based innovation not only enhances the competitiveness of SMEs but also provides more sustainable and socially responsible solutions. Start-ups that successfully implement these innovations tend to see improvements in reputation, customer satisfaction, and financial performance. Third, the environmental, social, and governance aspects of ESG have a significant impact on SME performance, helping them manage risks, seize new opportunities, and meet stakeholder expectations. Case study examples from various start-ups show that integrating ESG principles can provide competitive advantages and support sustainable growth.